If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3)(4y + -12) = 0 Reorder the terms: (3 + x)(4y + -12) = 0 Reorder the terms: (3 + x)(-12 + 4y) = 0 Multiply (3 + x) * (-12 + 4y) (3(-12 + 4y) + x(-12 + 4y)) = 0 ((-12 * 3 + 4y * 3) + x(-12 + 4y)) = 0 ((-36 + 12y) + x(-12 + 4y)) = 0 (-36 + 12y + (-12 * x + 4y * x)) = 0 (-36 + 12y + (-12x + 4xy)) = 0 Reorder the terms: (-36 + -12x + 4xy + 12y) = 0 (-36 + -12x + 4xy + 12y) = 0 Solving -36 + -12x + 4xy + 12y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + -12x + 4xy + 36 + 12y = 0 + 36 Reorder the terms: -36 + 36 + -12x + 4xy + 12y = 0 + 36 Combine like terms: -36 + 36 = 0 0 + -12x + 4xy + 12y = 0 + 36 -12x + 4xy + 12y = 0 + 36 Combine like terms: 0 + 36 = 36 -12x + 4xy + 12y = 36 Add '-12y' to each side of the equation. -12x + 4xy + 12y + -12y = 36 + -12y Combine like terms: 12y + -12y = 0 -12x + 4xy + 0 = 36 + -12y -12x + 4xy = 36 + -12y Reorder the terms: -36 + -12x + 4xy + 12y = 36 + -12y + -36 + 12y Reorder the terms: -36 + -12x + 4xy + 12y = 36 + -36 + -12y + 12y Combine like terms: 36 + -36 = 0 -36 + -12x + 4xy + 12y = 0 + -12y + 12y -36 + -12x + 4xy + 12y = -12y + 12y Combine like terms: -12y + 12y = 0 -36 + -12x + 4xy + 12y = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(-9 + -3x + xy + 3y) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-9 + -3x + xy + 3y)' equal to zero and attempt to solve: Simplifying -9 + -3x + xy + 3y = 0 Solving -9 + -3x + xy + 3y = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + -3x + xy + 9 + 3y = 0 + 9 Reorder the terms: -9 + 9 + -3x + xy + 3y = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -3x + xy + 3y = 0 + 9 -3x + xy + 3y = 0 + 9 Combine like terms: 0 + 9 = 9 -3x + xy + 3y = 9 Add '-3y' to each side of the equation. -3x + xy + 3y + -3y = 9 + -3y Combine like terms: 3y + -3y = 0 -3x + xy + 0 = 9 + -3y -3x + xy = 9 + -3y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -7/10=n/15 | | m=4(7) | | 2/7x-6=10 | | f(x)=75x+250 | | 6/4-3=2 | | 3.5x+20=90 | | x+3(x+2)=51 | | 6(-6x+2)=-168 | | 6(4w-5)=-27(7-w) | | 8x+9=8x+1 | | 2w+10=7q | | 4-3x=x-14 | | c+4d=8 | | (y/8y-44)=(2/x-2) | | 19=-5x+14 | | .04x+2=.8 | | -10/13=cos180/28(x-15) | | 3.5c-28+c=12.5 | | 3(7x-5)=4(5x+2) | | 4(w)-3=-27 | | -5r+2=-7r-12 | | 7r-18+19+40= | | -5r+2=-7r | | b^2/b^-2 | | -1+2(6x-5)=-107 | | x+1.6=2.1 | | -6(x-5)-4x=110 | | t/32=8 | | 0.3(2z+7)+11.1=0.7(2z-4) | | 15z^2=180 | | -3(3k-6)=72 | | 4=3y+2 |